VALIDITAS DIAGNOSTIK BIOPSI ASPIRASI JARUM HALUS PADA KARSINOMA PAYUDARA - Novrial, Dody (MANDALA of Health, 2010)
Breast cancer incidence is still in the second position after cervical cancer within womenmalignancy. Fine needle aspiration biopsy (FNAB) has been widely known and used in diagnosing breastlesions last few decades. FNAB diagnostic procedure is considered less invasive and relatively lessexpensive than surgery biopsy. This research was diagnostic study with cross sectional design. Researchdone by reading FNAB cytology and histopathology slides from 86 patients with breast tumor betweenJanuary 2004 until December 2007. WHO classification and Elston & Ellis method was used to diagnosebreast tumor variant and grading. While fnab cytology used the NHS Breast Screening Program(NHSBSP) guidelines. Diagnostic tests of FNAB showed sensitivity 91%, specificity 79%, and accuracy87%. The sensitivity and specificity values of FNAB on this research was still quite high, because in manyliterature explained that the sensitivity and specificity rates of FNAB ranged between 66% and 92%depending on the experience of diagnostic and hospital procedure